Islamic Marketing in Era Society 5.0 Based on Maqashid As-Syariah Approach - Siti Majidah (Review of Islamic Economics and Finance, 2022)
Purpose - The purpose of this study is to find out the opportunities and challenges of marketing digitalization by adjusting the 4P mix (Product, Price, Place, and Promotion) in a sharia marketing perspective and to analyze strategies that can be used in marketing in the era of society 5.0 based on sharia maqashid. The development of a very dynamic marketing concept from the era of society 1.0 to 5.0 requires companies to make various kinds of progressive breakthroughs in winning market share and loyalty from customers for a long time (long term relations) while still paying attention to the principles of maqashid sharia, namely Mashlahah for the community all stakeholders.Methodology - The research method used is qualitative research with a literature study approach. The results of the study indicate that marketing in the era of society 5.0 which is based on marketing digitalization still requires 4P marketing mix based on sharia values. Artificial Intelligence (AI) requires innovation, efficiency, and Islamic values, one of which is by using the Next Tech and New CX methods in marketing to provide a better customer experience. efficient, and businesses can provide added value to customers. Findings - To win the global competition in digital marketing, a marketer is also required to have several competencies such as; Innovative, Open-minded, agile, IoT friendly, dynamic and collaborative, and religious, while still prioritizing the spiritual values of marketers.Keywords: Islamic Marketing, Maqashid Syariah